Assessment of electron beam irradiation induced proteomic changes and its effect on the development of silkworm, Bombyx mori (Bombycidae: Lepidoptera) - Mani Kannan (Journal of Basic and Applied Zoology, 2016)
The present study has been designed to determine the hemolymph protein changes induced by EBI using Microtron (ranges from 20 to 100 Gy) on the 5th instar larvae of silkworm, Bombyx mori using SDS–PAGE. The EBI did not caused any impact on 5th instar larval hemolymph proteins, however a significant reduction of pupal hemolymph proteins such as lipophorin (250 kDa), vitellogenin (180 kDa), storage protein (76–80 kDa) and a 30 kDa protein was observed through SDS–PAGE and densitometry analysis. These proteins are known to play a crucial role in various developmental processes including transport of lipids, as amino acid reservoir for providing precursors for egg and cuticle formation and immunity of B. mori. Further, a decrease of antioxidant enzymes such as Superoxide Dismutase (SOD) and Catalase (CAT) in the EBI treated larval and pupal hemolymph was observed. In addition, a negative influence on growth characteristics and appearance of pupal deformity was noted. This may be due to damage in hemolymph proteins, when the larvae were exposed to EBI at >80 Gy.